기술 융합형 웹툰 이용자의 이용의도에 영향을 미치는 요인들에 대한 연구 - 장성원(Sung-Won Jang); 성동규(Dong-Kyoo Sung) (한국콘텐츠학회 논문지, 20(2), 2020)
This research was trying to examine through the technology acceptance model that is expanded in order to make an inquiry the factors having an effect on the acceptance intention of the technology fusion type webtoon user. The survey was carried out for the research for 114 questionnaire respondents where there is the technology fusion type webtoon utilization experience. After and hierarchical regression analysis was performed and the relationship was analyze between the factor. The total 13 hypotheses and one research problems were set and the study with was proceeded. Next, it is same if the results of study is summarized. Firstly, the interactivity and immersion, that is the subordinate factor of the Siljaegam, affected the static influence to the perceived usability. Secondly, with having the static influence an effect on the technology fusion type webtoon use intention the perceived usability was confirmed. Thirdly, the effeciency, Tendency of Conciseness, and consistency were the technology fusion type GUI standard extracted with the Ttamsaekjeok the result subfactor that it analize factor. Finally, with giving the meaningful influence to the perceived easiness the visual unrefined copper steam, that is the subordinate factor of the Siljaegam, was confirmed. 본 연구는 기술 융합형 웹툰 이용자의 수용의도에 영향을 미치는 요인들을 알아보기 위해 확장된 기술수용 모델을 통해 살펴보고자 하였다. 연구를 위해 기술 융합형 웹툰 이용 경험이 있는 설문 응답자 114명을 대상으로 설문조사를 실시하였다. 이후, 위계적 회귀분석을 실시하여 변인 간 관계를 분석하였다. 총 13개의 가설, 1개의 연구문제를 설정하여 연구를 진행하였다. 연구 결과를 요약하면 다음과 같다. 첫째, 실재감의 하위 요인인 상호작용성, 몰입은 인지된 유용성에 정적인 영향을 미쳤다. 둘째, 인지된 유용성은 기술 융합형 웹툰 이용 의도에 정적 영향을 미치는 것으로 확인되었다. 셋째, 기술 융합형 GUI 척도를 탐색적 요인분석한 결과 하위 요인으로 효율성, 간결성, 일관성이 추출되었다. 마지막으로 실재감의 하위 요인인 시각적 생동김은 인지된 용이성에 유의미한 영향을 주는 것으로 확인되었다. 이 같은 연구 결과는 기존의 멀티미디어 기술적 요소만을 검증하는 연구가 아닌, 인간의 감정이나 심리적 요인을 통해 기술 융합형 웹툰의 이용의도에 영향을 미치는 변수를 파악하였다는 점에서 학술적 의의를 찾을 수 있다.